Role of subsea permafrost and gas hydrate in postglacial Arctic methane releases - Portnov, Aleksei D (UiT Norges arktiske universitet, 2015)
The papers of this thesis are not available in Munin. Paper I: 'Offshore permafrost decay and massive seabed methane escape in water depths > 20 m at the South Kara Sea shelf.' Alexey Portnov, Andrew J. Smith, Jürgen Mienert, Georgy Cherkashov, Pavel Rekant, Peter Semenov, Pavel Serov, Boris Vanshtein. Available in Geophysical Research Letters, vol. 40, 1–6 Paper II: 'Modeling the evolution of climate-sensitive Arctic subsea permafrost in regions of extensive gas expulsion at the West Yamal shelf.' Alexey Portnov, Jürgen Mienert, Pavel Serov. Available in Journal of Geophysical Research: Biogeosciences, vol. 119, issue 11, 2014 Paper III: 'Methane release from pingo-like features across the South Kara Sea shelf, an area of thawing offshore permafrost'. Pavel Serov, Alexey Portnov, Jürgen Mienert, Peter Semenov, Polina Ilatovskaya. (Manuscript). Published version available in Journal of Geophysical Research: Earth Surface, vol. 120, issue 8, 2015 Paper IV: 'Ice-sheet driven methane storage and release in the Arctic.' Alexey Portnov, Sunil Vadakkepulyambatta, Jürgen Mienert, Alun Hubbard (manuscript). Published version available in Nature Communications, vol 7, p 10314 (2016) Greenhouse gas methane is contained as gas hydrate, an icy structure, under the seabed in enormous amounts of Arctic regions. West Svalbard continental margin, which we investigated here, is one of these regions. Also, in the Russian Kara Sea the subsea permafrost is acting as a cap for the gas to be released in the future. But continuous expulsions of methane have been already observed in both places. This study shows how the subsea permafrost in the Kara Sea, and gas hydrate systems offshore West Svalbard, have evolved from the last ice age to the present day. The conclusions are based on integrated field geophysical and gas-geochemical studies as well as modeling of permafrost, gas hydrate reservoirs and Barents Sea ice sheet dynamics. It shows that continuous permafrost of the Kara Sea is more fragile than previously thought. It is ...